The Safety and Efficacy of Nusinersen in the Treatment of Spinal Muscular Atrophy: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kirellos Said Abbas; Mennatullah Mohamed Eltaras; Nahla Ahmed El-Shahat; Basel Abdelazeem; Mahmoud Shaqfeh; James Robert Brašić (Medicina, 2022)
Background and objectives: Spinal muscular atrophy (SMA) is a neurodegenerative disease that leads to progressive proximal muscle weakness and muscle atrophy. To assess the beneficial and adverse effects of nusinersen, a promising intervention for SMA, we conducted a systematic search and meta-analysis of the published randomized control trials (RCTs) of nusinersen for SMA. Materials and methods: Utilizing the Preferred Reporting for Systematic Review and Meta-Analysis (PRISMA), we searched PubMed, Scopus, Web of Science, Cochrane Central, and Clinicaltrials.gov from inception to 22 July 2021. Results: Three RCTs satisfying the inclusion and exclusion criteria covered 274 patients: 178 patients in the nusinersen group. Our results show a significant risk difference (RD) in the motor milestone response (RD: 0.51; 95% CI: 0.39, 0.62; p < 0.00001) and improvement in the HINE-2 score (RD: 0.26; 95% CI: 0.12, 0.40; p < 0.0003) in the nusinersen group compared to the control group. Moreover, a significant decrease in the risk ratio (RR) for severe adverse events (RR: 0.72; 95% CI: 0.57, 0.92; p = 0.007) and any adverse event leading to treatment discontinuation (RR: 0.40; 95% CI: 0.22, 0.74; p = 0.004) was observed. An insignificant result was found for any adverse effects (RR: 0.93; 95% CI: 0.97, 1.01; p = 0.14) and for serious adverse effects (RR: 0.81; 95% CI: 0.60, 1.07; p = 0.14). Conclusions: This review provides evidence that nusinersen treatment was effective in treatment for infants with SMA and was associated with fewer severe adverse events; however, more RCTs are needed to establish evidence.